Influence of silica source in the catalytic activity and heterogenity of mesoporous vanadosilicates - Shylesh, S.; Mirajkar, Subhash P.; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2005)
Vanadium-substituted ordered mesoporous silicates (V-OMS) were synthesized hydrothermally using two common silica sources, viz. fumed silica and tetraethyl orthosilicate, and their surface properties and catalytic activities were evaluated in the liquid phase oxidation of 1-napthol using aqueous H2O2 as an oxidant. The catalysts were characterized by XRD, N-2, adsorption-desorption, DRUV-vis and TPR to evaluate the mesostructural ordering and the local environment of vanadium in the MCM-41 matrix. Characterization data of the fresh calcined catalysts reveal a more ordered hexagonal structure for the V-MCM-41 catalyst prepared by using tetraethyl orthosilicate as the silica source while spent catalyst showed that the material is less stable than the V-MCM-41 catalyst prepared by using fumed silica as the silica source. Further, the observed differences in the selectivity behavior of extracted and calcined forms of both vanadium catalysts shows that the treatment conditions had a decisive role in the formation of extra framework metal species and further in the mesoscopic structural ordering. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 1-napthol; MCM-41; Mesoporous; Oxidation; Vanadium

Oxidative dehydrogenation of ethylbenzene over vanadia-alumina catalysts in the presence of nitrous oxide: structure-activity relationship - Shiju, N. R.; Anilkumar, Mettu; Mirajkar, Subhash P.; Gopinath, Chinnakonda S.; Rao, B. S.; Satyanarayana, C. V. (Journal of Catalysis, 2005)
A series of vanadia-alumina catalysts with different vanadia contents were prepared by a wet impregnation method. The influence of the local structure of vanadia in these catalysts on the oxidative dehydrogenation of ethylbenzene with nitrous oxide was investigated. The use of N2O as a co-feed remarkably enhanced the styrene yield compared with the use of N-2. Characterization of these vanadia catalysts by XRD, FTIR, UV-vis, TPR, XPS, and V-51 NMR techniques suggests that the nature of the VOx species depends on the vanadia loading: the predominant species are monomeric vanadia at lower loadings, two-dimensional polyvanadates at intermediate loadings, and bulk-like V2O5 and AlVO4 at higher loadings. The rate of oxidative dehydrogenation (ODH) of ethylbenzene per vanadium atom increases with vanadia loading and reaches a maximum at 10 wt%, the loading at which the surface predominantly contains polyvanadate species. The observed variation in the selectivity of products with vanadium loading indicates that the monomeric V5+ species favors dehydrogenation, whereas bulk-like V2O5 preferentially participates in the dealkylation of ethylbenzene. The vanadium species remains at a higher oxidation state in the presence of N2O, leading to a higher styrene yield. than in a N-2 atmosphere. The ODH turnover rates increased with decreasing energy of the absorption edge in the UV-vis spectrum, at low VOx coverages of less than one monolayer on the Al2O3 surface. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: absorption edge energy; Alumina; ethylbenzene; Nitrous oxide; oxidative dehydrogenation; polyvanadates; styrene; vanadia

Silicotungstate-modified zirconia as an efficient catalyst for phenol tert-butylation - Devassy, Biju M.; Shanbhag, G. V.; Mirajkar, Subhash P.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2005)
The alkylation of phenol with tert-butanol was investigated using zirconia modified with silicotungstic acid (STA) as catalysts. The catalysts with different STA loading (5-25 wt.% calcined at 750 degrees C) and calcination temperature (15 wt.% calcined from 350 to 850 degrees C) were prepared and characterized by X-ray diffraction and NH3-TPD measurements. The XRD results indicate that STA stabilizes the tetragonal phase of zirconia. The catalyst with 15% STA on ZrO2 calcined at 750 degrees C shows the highest acidity and hence highest activity. Under the reaction conditions of 140 degrees C, tert-butanol/phenol molar ratio of 2 and LHSV of 4 h(-1), phenol conversion was 95.4% with selectivity to 2-tert-butyl phenol 4.3%, 4-tert-butyl phenol 59.2% and 2,4-di-tert-butyl phenol 35.8%. The reaction was studied as a function of time for 50 It without appreciable change in phenol conversion and product selectivity. The deactivated catalyst could be regenerated by calcination with out appreciable lose in catalytic activity and product selectivity. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: phenol; Silicotungstic acid; tert-butylation; Zirconia

Novel three dimensional cubic Fm3m mesoporous aluminosilicates with tailored cage type pore structure and high aluminum content - Srinivasu, Pavuluri; Alam, Sher; Balasubramanian, Veerappan V.; Velmathi, Sivan; Sawant, Dhanashri P.; Boehlmann, Winfred; Mirajkar, Subhash P.; Ariga, Katsuhiko; Halligudi, Shivappa B.; Vinu, Ajayan (Advanced Functional Materials, 2008)
Novel three dimensional cubic Fm3m mesoporous aluminosilicates (AIKIT-5) with very high structural order and unprecedented loadings of Al in the silica framework have been successfully prepared for the first time by using non ionic surfactant as a template in a highly acidic medium. The obtained materials have been unambiguously characterized in detail by several sophisticated techniques such as XRD, N, adsorption, HRTEM, HRSEM, EDS, elemental mapping, Al-27 MAS NMR, and NH3-TPD. We also demonstrate that the nature, and the amount of Al incorporation in the silica framework can easily be controlled by simply varying the n(H2O)/n(HCl) and the n(Si)/n(Al), ratios, and the Al sources in the synthesis gel. Among the Al sources examined, the Al isopropoxide (AiPr) is superior over other Al sources. Al-27 MAS NMR results reveal that the amount of tetrahedral Al in the framework can be controlled by simply adjusting the nSi/nAl ratio in the synthesis gel, which increases with increasing the Al incorporation. One of the interesting findings in the work is the increase of the specific surface area, specific pore volume and the pore diameter of AIKIT-5 with increasing the Al incorporation in the silica framework (up to n(Si)/n(Al), ratio of 10) while retaining the well-ordered three dimensional cage type porous structure, and the mechanism for the unusual behavior has been discussed in detail. Finally, the acidity and the catalytic activity in the acetylation of veratrole of the AIKIT-5 catalysts have been studied and the results have been compared with the several zeolites catalysts. Among the catalysts examined, AIKIT-5(10) is found to be superior over the zeolites catalysts such as mordenite, zeolite H-Y, zeolite H-beta, and ZSM-5.

MCM-41 supported phosphotungstic acid for the hydroxyalkylation of phenol to phenolphthalein - Jha, Ajay; Garade, Ajit C.; Mirajkar, Subhash P.; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2012)
A novel application of phosphotungstic acid, H3PW12O40 (PWA) supported on MCM-41 molecular sieve as a solid acid catalyst has been demonstrated for the synthesis of phenolphthalein by hydroxyalkylation of phenol and phthalic anhydride. PWA/MCM-41 (20%) showed the highest activity as compared to that of parent PWA and MCM-41 individually, due to the excellent dispersion of PWA on MCM-41 leading to the redistribution of Bronsted and Lewis acid sites on MCM-41. The effect of PWA loading on phthalic anhydride conversion and phenolphthalein selectivity was also studied. All these prepared catalysts were characterized by XRD, N-2 adsorption-desorption isotherm, pyridine-FTIR, and NH3-TPD. The effect of various reaction parameters, namely, mole ratios, catalyst concentration, temperature, reaction time, and percentage of PWA present in the catalysts on conversion and selectivity of products has been also investigated. The utility of 20% PWA/MCM-41 catalyst was established by its efficient activity for hydroxyalkylation of phenol and p-cresol with formaldehyde to the corresponding dihydroxydiarylmethane products.